Increasing Activeness and Multiplication Learning Achievement through Demonstration Methods in Class III Students of SDN 1 Sawahan - Febriana Mutiara Puspitasari (Universitas Sebelas Maret, 2022)
The purpose of this study was to increase the activity and achievement in learning multiplication through demonstration methods in class III students of SDN 1 Sawahan. The research conducted was classroom action research with two cycles. Each cycle consists of two meetings and four stages, namely planning, implementing action, observing, and reflecting. The subjects were 15 students of grade III SDN 1 Sawahan. Data collection techniques through test techniques (actions) and non-test (observation and documentation). The increase in the activeness of learning mathematics is evidenced by the increased activity in each cycle, namely before the act of student activity was 47%, the first cycle was 73%, and the second cycle was 87%. The increase in the percentage of multiplication learning outcomes from the pre-cycle was 33%, the first cycle was 67%, and the second cycle was 100%. From the activities of the pre-cycle, cycle I, and cycle II, it can be concluded that there is an increase in the activity and learning achievement of multiplication through the demonstration method in class III students at SDN 1 Sawahan.